"Gigantic" biatrial myxoma with right heart functional impairment. Issue 7 (11th May 2018) - Vega Adauy, Julián; Gabrielli, Luigi; Córdova, Samuel; McNab, Paul; Saavedra, Rodrigo; Piñeiro, Marta; Zalaquett, Ricardo
Abstract : Cardiac myxomas are frequently located in the left or right atria, with multiple locations being rare. We report a 59‐year‐old healthy female with 5 months of cough and exertional dyspnea. A transthoracic echocardiography (TTE) exhibits a 9 × 5 cm nonpedunculated tumor arising from the interatrial septum (IAS) and inhabiting both atria, but was unable to depict the relation with the IAS. Transesophageal echocardiography exposes a single tumor crossing the IAS through an ostium secundum atrial septal defect (ASD) causing right heart functional impairment. Uneventful cardiac surgery allowed complete resection of the lesion and ASD closure. Pathology reported a myxoma.